Indonesian Islam in a New Era: How Women Negotiate Their Muslim Identities by Susan Blackburn, Bianca J. Smith, and Siti Syamsiyatun, eds. (Victoria, Australia: Monash University Press, 2008. 212 pages.) (American Journal of Islam and Society, 2009)
This work examines the negotiations that Indonesian Muslim women havemade in certain areas of life in the post-Suharto era, an era of socio-politicalreform in which “it is possible to question accepted attitudes and break newground” (p. 16), and their religious practices and identities. The editorsclaim that their work breaks new ground in that (a) it informs readers of“how the women themselves experience their religion and actively engagewith it in their lives” (p. 1); (b) it focuses on women and Islam in the post-Suharto period, in which Islam is more prominent and it is more acceptableto put forward feminist views in Indonesia and within Islam; and (c) it isthe effort of insiders – Indonesian women with western and Islamic training– who can bridge the gap between western and Indonesian scholarshipon Islam and women. The editors state up front that the book does notdeliberately engage in a critical feminist theory and that they are not feministwriters; rather, they are influenced by feminism and desire to show thatwomen are active participants and not mere “passive victims of maleoppression” (p. 2) ...